LEGAL ISSUES OF DEVELOPMENT AND REFORM OF TAX ADMINISTRATION PROCEDURES - Ustynova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this study is to examine the development of the tax administration system, identify current challenges and substantiate ways to improve it, taking into account international experience and modern digital technologies. Research methods: the article uses the following general scientific methods of research: observation and description and theoretical methods: analysis, generalisation, explanation, as well as systemic, functional, specific sociological. The research is based on the study of the regulatory framework of Ukraine and the European Union, recommendations of the Organisation for Economic Co-operation and Development (OECD), analysis of court practice in the field of tax disputes, as well as statistical materials on the efficiency of tax administration. The study applies general scientific methods of analysis and synthesis, a comparative legal approach to the analysis of tax systems of foreign countries, system analysis and the method of legal modelling. The results obtained show that over the past ten years, the tax administration system has undergone significant changes caused by the introduction of digital technologies and automation of control procedures. In particular, many countries have introduced automated platforms for tax risk assessment, which has significantly reduced tax evasion. Ukraine has also implemented a number of reforms aimed at simplifying tax procedures, developing electronic services and ensuring transparency of tax authorities. At the same time, challenges remain, including insufficient integration of tax databases, limited international exchange of tax data and the complexity of tax administration for small and medium-sized businesses. The results obtained can be used as a basis for developing innovative approaches to reforming tax administration and improving the efficiency of tax policy in Ukraine. Discussion: tax administration plays a leading role in ensuring the stable functioning of the modern tax system, as it is aimed at efficient management of tax revenues and strengthening the fiscal sustainability of the state. In the context of globalisation, digital transformation of the economy and growing tax competition between countries, there is a need to improve tax administration mechanisms. At the same time, tax authorities face challenges such as tax evasion, the expansion of the shadow sector and the need to harmonise tax legislation in line with international standards.